Projeto de promoção de saúde de mulheres em abrigos atendidos pela FAMED-HCPA - Barreto Nolibos, Vinicius; Jun Cervera Sei, Leonardo; Pirih Pecoits, Rodrigo; Oliveira Galão, Adriani; Bauermann Leitão, Cristiane; Severo Garcia, Tiago; Helena Rech, Tatiana (Revista da Extensão, 2024)
Projeto de promoção de saúde de mulheres em abrigos